2015
DOI: 10.1152/ajpregu.00279.2014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing hepatic mitochondrial fatty acid oxidation stimulates eating in food-deprived mice

Abstract: (FAO) has long been implicated in the control of eating. Nevertheless, direct evidence for a causal relationship between changes in hepatic FAO and changes in food intake is still missing. Here we tested whether increasing hepatic FAO via adenovirusmediated expression of a mutated form of the key regulatory enzyme of mitochondrial FAO carnitine palmitoyltransferase 1A (CPT1mt), which is active but insensitive to inhibition by malonyl-CoA, affects eating and metabolism in mice. CPT1mt expression increased hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…The decrease in RQ appeared during the dark period when animals are active, eat more, and normally tend to utilize more carbohydrates than fat (26). The increase in fat utilization over longer periods of time may, at least in part, explain the decrease in body weight and change in body composition seen both in the present study and in previous studies (11).…”
Section: Discussionsupporting
confidence: 67%
“…The decrease in RQ appeared during the dark period when animals are active, eat more, and normally tend to utilize more carbohydrates than fat (26). The increase in fat utilization over longer periods of time may, at least in part, explain the decrease in body weight and change in body composition seen both in the present study and in previous studies (11).…”
Section: Discussionsupporting
confidence: 67%
“…CPT1A is the rate-limiting enzyme for β-oxidation of long-chain fatty acids, and activation of β-oxidation contributes to ATP production [ 32 ]. The overexpression of CPT1 has been shown to enhance hepatic mitochondrial fatty acid oxidation in mice [ 33 ]. KMP increased the protein expression of CPT1A in parallel with its gene expression in HepG2 cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, an inverse relationship between the liver-specific modulation of fatty acid oxidation and mitochondrial energy metabolism [33][34][35][36] or associated secondary changes in liver FAO and mitochondria gene expression has been observed with chronic diet-induced weight gain [37,38]. However, others have observed an increased food intake in mice with increased liver FAO following the overexpression of CPT-1 [39]. Our previous findings suggested that the differences in acute HFHS-induced weight gain, body composition changes, and the regulation of food/energy intake are inversely associated with liver tissue PGC1a expression, fatty acid oxidation, and mitochondrial respiratory capacity [40][41][42].…”
Section: Discussionmentioning
confidence: 99%